A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF BINA INSAN VOCATIONAL HIGH SCHOOL SIAK HULU IN COMPREHENDING RECOUNT TEXTS - Esti Raihana Raihana; Effendy Gultom Gultom; M. Syarfi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study is to find out the second year students’ ability of Bina Insan Vocational High School Siak Hulu in comprehending recount texts. This research focuses on finding factual information, finding main ideas, locating the meaning of vocabulary in context, identifying references, and making inferences based on recount texts. Data were collected using reading comprehension test with multiple choice type. The test contained 30 items. The try out was conducted to check the validity and reliability of the test. The research findings are as follows: first, the ability of the students in comprehending recount texts is 51 which is in mediocre level. Second, the students’ mean score in finding factual information is 60, the mean score in finding main ideas is 41, the mean score in locating the meaning of vocabulary in context is 69, the mean score in identifying references is 68, and the mean score in making inferences is 68. The highest score obtained by the students is in finding the meaning of vocabulary in context that falls into good ability level, and the lowest score that the students get is in finding main ideas that falls into mediocre ability level. Keywords: Ability, Comprehending, Recount Texts.